Label-Free Assay of Protein Kinase A Activity and Inhibition Using a Peptide-Based Electrochemical Sensor - Hyunju Cho; Chang-Seuk Lee; Tae Hyun Kim (Biomedicines, 2021)
We propose a simple label-free electrochemical biosensor for monitoring protein kinase activity and inhibition using a peptide-modified electrode. The biosensor employs cys-kemptide (CLRRASLG) as a substrate peptide which was immobilized on the surface of a gold electrode via the self-assembly of the thiol terminals in cysteine (C) residues. The interaction between protein kinase A (PKA) and adenosine 5′-triphosphate (ATP) on the cys-kemptide immobilized electrode can cause the transfer of ATP terminal phosphates to the peptide substrates at serine (S) residues, which alters the surface charge of the electrode, thus enabling monitoring of the PKA activity via measuring the interfacial electron transfer resistance with electrochemical impedance spectroscopy. The proposed sensor showed reliable, sensitive, and selective detection of PKA activity with a wide dynamic range of 0.1–100 U/mL and a detection limit of 56 mU/mL. The sensor also exhibited high selectivity, rendering it possible to screen PKA inhibitors. Moreover, the sensor can be employed to evaluate the activity and inhibition of PKA in real samples.